Identification of Lecturer Difficulties in Implementing of Blended Learning in the Covid-19 era - Herliana, Fitria; Halim, Abdul; Farhan, Ahmad; Kasli, Elisa (Asian Journal of Science Education, 2020)
Learning in the Covid-19 era requires lecturers and students not to study in the same place. This condition is a new challenge for lecturers and students to continue implementing effective learning using a suitable approach that is blended learning. This research is a preliminary study to determine the difficulties of lecturers in implementing blended learning at Department of Physics Education, FKIP Universitas Syiah Kuala. The method used in this research is a survey using a questionnaire containing 30 statements. The indicators measured in this study were 9 (nine) indicators from 2 aspects, namely the readiness and skills of lecturers in implementing blended learning in the Covid-19 era. The questionnaire was distributed to 15 lecturers in the Department of Physics Education, and the results of the responses obtained were analyzed using descriptive statistics. The results of the analysis show that 29.23% of lecturers are not ready to apply the blended learning approach because 53.85% of lecturers rarely access the internet and learning platforms to facilitate lecture activities, so they are not used to using it. 44% of lecturers are not yet skilled in using learning platforms which are shown by 46.16% of lecturers having difficulty changing the general appearance of the virtual class, and 46.15% of lecturers have difficulty interacting using the learning platform. These difficulties are the obstacles for lecturers to apply the blended learning approach in lecture activities, so it is necessary to immediately find solutions to help the lecturer difficulties so that lectures in the Covid-19 era continue to run effectively like previous lectures.Keywords: Blended Learning, Covid-19, Lecturer Difficulties, Obstacles